Evaluation of hip joint range of motion inmechanicalchronic low back pain-An observational study - D.MALARVIZHI,; M. KISHOREKUMAR, (International Journal of Pharma and Bio Sciences, 2016)
Low back pain is one of the major cause for frequent medical consultation among world. In most of the cases reasons were unknown. Now a days people are using hip movements at reduced rate in day to day life which became one of the serious factors for causing low back pain. The main aim of the study was to check the hip range of motion for mechanical chronic low back pain patients. Study design was non experimental and study type was observational and sub type was cross sectional. 120 Subjects were selected applying both inclusion and exclusion criteria. Using goniometry hip joint range of motion was calculated. The result of the study confirms that hip joint range of motion was greatly reduced for mechanical chronic low back pain patients. The study concluded that there was significant reduction in hip joint range of motion for mechanical chronic low back pain patients. So Physiotherapy intervention for chronic low back pain patients should include hip joint range of motion exercises.